Perbandingan Media Internasional: CNN dan Al-Jazeera Terkait Serangan Udara Pasukan Hamas ke Israel - Rinaldy, Asfar (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2023)
This research focuses on how or how international online media present news about "Hamas Air Strikes on Israel" on topics focused on two international media namely CNN and Al Jazeera by looking at the comparison between the two media related to existing events. Using the research method Framing Analysis model Robert N. Entman. The practice of framing in the context of the media involves the selection of certain issues, neglect of other issues, and the prominence of certain aspects of the issue through various striking placement discourse strategies and is one of the alternative theories to obtain an overview of the content of the message conveyed and know how the media constructing reality. Framing analysis is more qualitative. With data collection techniques used are primary sources, and secondary sources. As for the results of this study, the authors found that CNN represents Israel positively and Hamas negatively. On the other hand, Al Jazeera represents Hamas positively and Israel negatively. In the news discourse presented by Al Jazeera media, there are also often nuances more towards support for Hamas, with many sources and participants involved from their faction. In the news discourse presented by CNN media, there are often anti-Hamas nuances where the sources and participants involved, namely most of the Israelis.